2004
DOI: 10.1152/ajpcell.00197.2004
|View full text |Cite
|
Sign up to set email alerts
|

Different modes of sodium-d-glucose cotransporter-mediated d-glucose uptake regulation in Caco-2 cells

Abstract: We recently reported that a considerable amount of the sodium-d-glucose cotransporter SGLT1 present in Caco-2 cells, a model for human enterocytes, is located in intracellular compartments attached to microtubules. A similar distribution pattern was also observed in enterocytes in thin sections from human jejunum, highlighting the validity of the Caco-2 cell model. Fluorescent surface labeling of live Caco-2 cells revealed that the intracellular compartments containing SGLT1 were accessible by endocytosis. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…Subsequently, Khoursandi et al (21) reported that the intracellular compartments containing SGLT1 are accessible by endocytosis during incubation of the cells for 30 min at 37°C. Incubation of Caco-2 cells with mastoparan, a drug that enhances apical endocytosis, shifted a large amount of SGLT1 from the apical membrane to intracellular sites and significantly reduced sodium-dependent glucose uptake (Ϫ60%) (21). These papers showed that SGLT1 is internalized from the apical surface to the endosomes of Caco-2 cells by incubation of the cells for 30 min at 37°C and that most intracellular SGLT1 remains in the intracellular reserve pools.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequently, Khoursandi et al (21) reported that the intracellular compartments containing SGLT1 are accessible by endocytosis during incubation of the cells for 30 min at 37°C. Incubation of Caco-2 cells with mastoparan, a drug that enhances apical endocytosis, shifted a large amount of SGLT1 from the apical membrane to intracellular sites and significantly reduced sodium-dependent glucose uptake (Ϫ60%) (21). These papers showed that SGLT1 is internalized from the apical surface to the endosomes of Caco-2 cells by incubation of the cells for 30 min at 37°C and that most intracellular SGLT1 remains in the intracellular reserve pools.…”
Section: Discussionmentioning
confidence: 90%
“…In this work the authors did not distinguish whether the SGLT1 protein in the plasma membrane or the turnover of SGLT1 was increased. In another study in which Caco-2 cells were preincubated for 1 h with 100 mM D-glucose, a 45% decrease of phlorizin inhibitable AMG uptake was observed (20). The authors proposed that this down-regulation is due to increased endocytosis, however, no significant changes of the intracellular distribution of SGLT1 could be detected.…”
Section: Discussionmentioning
confidence: 98%
“…Cyclic AMP, protein kinase A, protein kinase C (PKC), 3 and phosphoinositol 3-kinase are involved in the regulatory pathways (13,14,16). It has been shown that SGLT1 can be regulated by changes in transcription (12,17,18), mRNA stability (19), intracellular trafficking (14,16,20,21), and transporter activity (22). However, the individual regulatory pathways, their cross-talk, and their physiological importance are not understood.…”
mentioning
confidence: 99%
“…Studies have revealed intracellular stores of SGLT1 (38,39), which are thought to play a role in the regulation of SGLT1-mediated glucose uptake. SGLT1 has also been shown to be rapidly upregulated by sweet taste receptors (76).…”
Section: Other Regulatory Mechanismsmentioning
confidence: 99%